Mini-Mental State Examination: Screening and Diagnosis of Cognitive Decline, Using New Normative Data - Santana, Isabel (2016)
Introduction: The Mini-Mental State Examination is the most commonly used cognitive screening test. In Portugal, the cut-off scores are defined according to literacy groups, but different proposals have been recommended by more representative studies. We therefore propose to confirm the influence of demographical variables, such as age and education, in the subject’s performance; evaluating the discriminant ability of the new normative data; and to further examine the diagnostic acuity of the validated cut-off scoring for mild cognitive impairment and for the most prevalent types of dementia.Material and Methods: Our study includes 1 441 educated subjects, divided into seven subgroups: Mild cognitive impairment, Alzheimer’s disease, frontotemporal dementia, vascular dementia, dementia with Lewy bodies, community-controls and memory clinic-controls.Results: Altogether age and education explain 10.4% of the Mini-Mental State Examination results variance, with both variables contributing significantly to the results’ prediction. The diagnostic acuity based on the most recent normative data was always higher than the one obtained through the validation cut-off scoring, revealing an overall excellent specificity (superior to 90%) and different sensitivity values: excellent for mild Alzheimer’s disease (91%), good for dementia with Lewy Bodies (78%) and low for mild cognitive impairment (65%), frontotemporal dementia and vascular dementia (55%).Discussion and Conclusions: The performance on the Mini-Mental State Examination is influenced by age and education, supporting the use of normative data that consider those variables. With this approach, the Mini-Mental State Examination could be a sensitive and specific instrument for the Alzheimer’s disease screening among all healthcare levels. Nevertheless, its diagnostic acuity is limited in other conditions frequently seen in memory clinics, such as Mild Cognitive Impairment and other types of dementia.